2009
DOI: 10.1239/jap/1261670689
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Parameter Binomial Approximation

Abstract: We approximate the distribution of the sum of independent but not necessarily identically distributed Bernoulli random variables using a shifted binomial distribution where the three parameters (the number of trials, the probability of success, and the shift amount) are chosen to match up the first three moments of the two distributions. We give a bound on the approximation error in terms of the total variation metric using Stein's method. A numerical study is discussed that shows shifted binomial approximatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Example 1. In this example we intend to convey the typical behaviour of the various approximations when applied to the Bayesian hierarchical modelling problem described in [24]. Table 1: Approximating distributions for the Poisson-binomial law.…”
Section: Comparison Of Distributional Approximationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Example 1. In this example we intend to convey the typical behaviour of the various approximations when applied to the Bayesian hierarchical modelling problem described in [24]. Table 1: Approximating distributions for the Poisson-binomial law.…”
Section: Comparison Of Distributional Approximationsmentioning
confidence: 99%
“…The Poisson-binomial distribution is the law of the number of successes in a sequence of independent, nonidentically distributed trials and, as such, has found utility in several modelling applications, including Bayesian heirarchical models [24], generalized linear models [15], and noisy threshold models [21]. What is more, as the convolution product of nonidentical two-point distributions, the Poisson-binomial distribution is also intimately linked to several combinatorial and occupancy problems [26], including the 'birthday paradox' [32].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it would be best to use only common distributions such as the binomial, Poisson or normal. In the article by Peköz et al [17], several different approximations to the distribution of the sum of independent Bernoulli random variables are considered and evaluated. A Poisson approximation performs well if the Bernoulli probabilities are all very small.…”
Section: Two Approaches For Finding An Approximate Modelmentioning
confidence: 99%
“…This then allows three parameters to be adjusted and, in most cases, three moments or three derivatives could be matched. The article by Peköz et al [17] evaluates all the approximations discussed here (and derives error bounds) over a range of different settings and finds that a translated binomial approximation performs the best. As we show later, our analysis demonstrates that a binomial approximation with two fitted parameters performs much better than the usual binomial approximation with one fitted parameter, and the three parameter binomial approximation does not perform much better than the two parameter binomial approximation-though it requires additional computations and data to be transmitted and stored.…”
Section: Two Approaches For Finding An Approximate Modelmentioning
confidence: 99%
“…The earliest work focused on the Poisson approximation, of which a detailed account can be found in [6]. Subsequently, variations of the Poisson law were used: Poisson-Charlier signed measures (see [6] and the references therein), (signed) compound Poisson [5], [9], [22], shifted Poisson [4], [13]; as were the binomial law and its variations: binomial [13], [17], [30], 'almost' binomial [33], signed binomial-Krawtchouk [28], (signed) compound binomial [10], [11], [12], shifted binomial [24], [27]. Among more recent work, a class of signed measures was introduced in [7] that yielded notably impressive approximations in the special case of counting records in an independent and identically distributed sequence, 746 M. SKIPPER a two-parameter polynomial birth-death distribution was proposed in [8], and an arbitrary Gibbs measure approximation was developed in [18].…”
Section: Introductionmentioning
confidence: 99%